THE IMPORTANCE OF PSYCHOLOGY IN ISLAMIC DA’WAH COMMUNICATIONS - Dian Mego Anggraini (Jurnal Konseling Pendidikan Islam, 2023)
This research is related to the urgency of the psychology of communication in Islamic da'wah communication. This title was raised when looking at the phenomenon of rejection of preachers by some elements of society. The method used by researchers is a qualitative research method with library research data sources regarding references related to communication psychology, communication science, and problems related to community da'wah. The findings of the research are that a da'i who has an understanding of communication psychology and communication science is able to convey da'wah material according to the various backgrounds of the congregation or audience he is dealing with. The researchers' conclusion is that the psychology of communication and the science of communication is something that a da'i must have, as evidenced by all of the preachers' congregational criteria, which are always related to the psychology of communication, such as exemplary behavior, empathetic nature, information transactions, mediation, collective vision, mission, and goals.